1994
DOI: 10.1159/000183943
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Epidermal Growth Factor and Transforming Growth Factor-Alpha in Fallopian Tube Epithelium and Their Role in Embryogenesis

Abstract: We studied the expression of epidermal growth factor (EGF) and transforming growth factor (TGF)-α in human fallopian tube epithelium at various menstrual stages. Immunohistochemical staining using anti-EGF and anti-TGF-α antibodies showed a specific staining in ampullary tube epithelium at late follicular and luteal stages but the staining was very weak at the early follicular stage. Quantitative reverse transcription and polymerase chain reaction (RT-PCR) using β-actin mRNA as an internal standard revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…In the negative conditioning, embryos are protected against oxidative stress and deleterious components which are regularly generated during in vitro embryo cultivation [20,34]. In the positive conditioning, embryo development is enhanced by the secretion of embryotrophic factors [35] such as leukemia inhibitory factor (LIF) [36,37], fibroblast growth factor (FGF) [38], epidermal growth factor (EGF) [39], and insulin-like growth factor (IGF) into the culture medium [35]. Our study could not provide enough evidences which mechanism have been most probably involved in the improvement of the embryo development following co-culture of embryos with either mouse or human embryonic fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In the negative conditioning, embryos are protected against oxidative stress and deleterious components which are regularly generated during in vitro embryo cultivation [20,34]. In the positive conditioning, embryo development is enhanced by the secretion of embryotrophic factors [35] such as leukemia inhibitory factor (LIF) [36,37], fibroblast growth factor (FGF) [38], epidermal growth factor (EGF) [39], and insulin-like growth factor (IGF) into the culture medium [35]. Our study could not provide enough evidences which mechanism have been most probably involved in the improvement of the embryo development following co-culture of embryos with either mouse or human embryonic fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Tubal mucosa and endometrium are sources of cytokines and growth factors which are necessary for embryos [31][32][33]. It is obvious the embryos cultured in vitro are deprived from majority of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry using hEGF antibody was employed in this study to determine the localization of EGF in A and I oviductal regions of P and C gilts. EGF has previously been detected by means of immunohistochemical techniques in human placental tissue and human oviductal tissue [25,30,31,43]. Chegini et al [31] demonstrated the expression of mRNA and protein for EGF, TGFa, and EGF-R in human fallopian tubes.…”
Section: Discussionmentioning
confidence: 99%
“…The tubal epithelial lining was the primary binding site of these three entities, with weaker immunostaining in stromal and smooth muscle cells. Kurachi et al [43] reported that EGF and TGFa were expressed in human oviductal epithelium at specific menstrual stages, with specific immunostaining being greater in ampullary tube epithelium at late follicular and luteal stages than at the early follicular stage. Kasselberg et al [44] used immunohistochemistry and hEGF antibody to localize EGF in a variety of human maternal and fetal tissues.…”
Section: Discussionmentioning
confidence: 99%